PENGELOLAAN PEMBELAJARAN BERBASIS KURIKULUM MERDEKA BAGI GURU OLAHRAGA JSIT WILAYAH BENGKULU - Citra Dewi; Rita Prima Bendriyanti; Suwarni; Megi Personi; Roky Saputra; Febi Puspasari; Agnes Monika Rahmadani; Alex Brata; Ilham Hidayat (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2023)
Freedom to Learn is an educational terms that is currently being promoted by the Minister of Education and Culture. It is hoped that the principle of Freedom to Learn can accelerate the process of education reform in Indonesia, which has so far been considered to be slowly withering. Kurikulum Merdeka Belajar is motivated by the results of the Program for International Student Assessment (PISA) which shows that 70% of students aged 15 years are below the minimum competence in understanding simple reading or applying basic mathematical concepts. This community service activity focuses on sports teachers in JSIT Bengkulu who are given training on the content of Kurikulum Merdeka and Profil Pancasila, then the implementation of Kurikulum Merdeka and Profil Pancasila in PJOK learning. The method used in this activity is Lectures on the Content of Kurikulum Merdeka and Profil Pancasila students, the Implementation of Kurikulum Merdeka and Profil Pancasila in PJOK learning). Evaluation of the success of this activity is carried out smoothly and well. The response of the participants during this activity was very positive and very enthusiastic. Where the theme of this activity is useful for all sports teachers who are members of JSIT in carrying out kurikum merdeka belajar learning.